Digitalisasi Manajemen Pendidikan: Tantangan dan Peluang di Era Teknologi - Muh. Hasbi (Al-Buhuts, 2023)
Digitalization has become one of the primary factors driving the transformation of modern educational systems, particularly in the field of educational management. The rapid development of information and communication technology has encouraged educational institutions to shift from conventional management systems to digital-based systems that are more effective, efficient, and transparent. This study aims to analyze the various opportunities and challenges associated with the digitalization of educational management in the technological era. The research employed a library research method using a descriptive qualitative approach. Data were collected through an extensive review of books, scientific articles, national and international journals, and relevant academic documents published between 2003 - 2023. The data analysis technique utilized content analysis by identifying major themes related to the digitalization of education. The findings indicate that the digitalization of educational management offers several strategic opportunities, including improved efficiency in educational administration, accelerated academic services, easier access to data and information, data-driven decision-making, and enhanced transparency and accountability in educational governance. Furthermore, the utilization of digital technology supports the flexibility of educational services and strengthens the quality of institutional governance in the modern era. However, the implementation of digitalized educational management continues to face several challenges, such as limited technological infrastructure, low levels of digital competence and literacy among human resources, resistance to organizational change, and concerns regarding data security and user privacy. This study concludes that the successful implementation of digitalized educational management requires adequate technological infrastructure, the enhancement of digital competencies among educators and educational staff, the development of integrated information systems, and government policies that are adaptive to technological advancements. With appropriate strategies, the digitalization of educational management can serve as an effective solution for improving the quality, effectiveness, and competitiveness of education in the era of digital transformation